TARKHANISM IN MEDIEVAL GEORGIA AND ARMENIA: FEATURES OF THE TRANSCAUCASIAN FEUDALISM - Маргарян, Гор Араратович (History, Archeology and Ethnography of the Caucasus, 2023)
From the early Middle Ages, the term “tarkhan” found its way into the lexicon of the Transcaucasian peoples, initially associated with the Khazar realm. As the Mongol conquests unfolded, the word “tarkhan” and the phenomenon itself made their way into the historical narratives of Armenia and Georgia. In its early interpretation, “tarkhan” primarily signified exemption from taxes, though this was only one facet of its meaning. Over time, tarkhanism, as a form of immunity from various obligations and responsibilities, gained prominence within the evolving framework of feudalism. This article aims to collect and analyze information from diverse sources, including Armenian, Georgian, and Persian accounts, to understand the use and significance of tarkhanism within the Transcaucasian feudal systems. The study delves into the evolution of tarkhanism in medieval Georgia and Armenia through comparative analysis. Furthermore, it explores how the Georgian and Armenian churches became recipients of this form of immunity, shedding light on the conditions and terms associated with tarkhanism. Beyond a brief exploration of the term’s etymology and primary meaning, the article addresses several key questions: How was the concept of tarkhanism perceived in the Georgian and Armenian contexts prior to the Mongol conquest? What were the specific evolutions and implications of tarkhanism in these regions during the medieval period? Did tarkhanism encompass more specific privileges, such as tax exemptions? How and why did the church come to hold the status of tarkhanism? These questions collectively contribute to a deeper understanding of tarkhanism and its role in shaping the historical landscapes of Georgia and Armenia during the medieval era.
Keywords: Georgia; Armenia; Medieval Age; Tarkhans; Tarkhanism; Immunity; Taxes; Privileges; Georgian Church; Feudalism